APPLICATION OF COMPLEX-TRACE ANALYSIS TO SEISMIC DATA FOR RANDOM-NOISE SUPPRESSION AND TEMPORAL RESOLUTION IMPROVEMENT - Karsli H.; Dondurur D.; Çifçi G. (My University, 2006)
Time-dependent amplitude and phase information of stacked seismic data are processed independently using complex trace analysis in order to facilitate interpretation by improving resolution and decreasing random noise. We represent seismic traces using their envelopes and instantaneous phases obtained by the Hilbert transform. The proposed method reduces the amplitudes of the low-frequency components of the envelope, while preserving the phase information. Several tests are performed in order to investigate the behavior of the present method for resolution improvement and noise suppression. Applications on both 1D and 2D synthetic data show that the method is capable of reducing the amplitudes and temporal widths of the side lobes of the input wavelets, and hence, the spectral bandwidth of the input seismic data is enhanced, resulting in an improvement in the signal-to-noise ratio. The bright-spot anomalies observed on the stacked sections become clearer because the output seismic traces have a simplified appearance allowing an easier data interpretation. We recommend applying this simple signal processing for signal enhancement prior to interpretation, especially for single channel and low-fold seismic data. © 2006 Society of Exploration Geophysicists. All rights reserved.
Keywords: GEOPHYSICAL SIGNAL PROCESSING; HILBERT TRANSFORMS; SEISMOLOGY